2019
DOI: 10.1097/anc.0000000000000581
|View full text |Cite
|
Sign up to set email alerts
|

Eat, Sleep, Console Approach

Abstract: Background: The opioid epidemic in the United States has resulted in an increased number of drug-exposed infants who are at risk for developing neonatal abstinence syndrome (NAS). Historically, these infants have been treated with the introduction and slow weaning of pharmaceuticals. Recently, a new model called Eat, Sleep, Console (ESC) has been developed that focuses on the comfort and care of these infants by maximizing nonpharmacologic methods, increasing family involvement in the treatment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(29 citation statements)
references
References 12 publications
1
20
0
Order By: Relevance
“…This approach was devised to reduce the amount of opioids required by infants for NOWS management and to shorten hospitalizations for NOWS infants. Studies have shown that the ESC approach is a promising intervention for the management of NOWS infants (Achilles and Castaneda-Lovato 2019;Blount et al 2019;Dodds et al 2019;Grisham et al 2019;Parlaman et al 2019). It is unclear whether there is sufficient evidence to recommend the ESC approach as part of standard-of-care.…”
Section: Assessment and Diagnosismentioning
confidence: 99%
“…This approach was devised to reduce the amount of opioids required by infants for NOWS management and to shorten hospitalizations for NOWS infants. Studies have shown that the ESC approach is a promising intervention for the management of NOWS infants (Achilles and Castaneda-Lovato 2019;Blount et al 2019;Dodds et al 2019;Grisham et al 2019;Parlaman et al 2019). It is unclear whether there is sufficient evidence to recommend the ESC approach as part of standard-of-care.…”
Section: Assessment and Diagnosismentioning
confidence: 99%
“…The assessment and management of NOWS has been problematic, 16,38 in part because extant assessments rely on the subjective observations of health care professionals. 10,39 The findings of this cohort study suggest that acoustic cry analysis has potential as an objective measure of opioid withdrawal in the neonate. Cross-validated random forest models trained using newborn cry acoustics were able to generate accurate predictions (AUC, 0.90; accuracy, 0.85; sensitivity, 0.89; specificity, 0.83).…”
Section: Discussionmentioning
confidence: 80%
“…The assessment and management of NOWS has been problematic, in part because extant assessments rely on the subjective observations of health care professionals . The findings of this cohort study suggest that acoustic cry analysis has potential as an objective measure of opioid withdrawal in the neonate.…”
Section: Discussionmentioning
confidence: 92%
“…If the infant's function is significantly affected, pharmacologic treatment may be necessary. 15 If eating, sleeping, and consolability are not disrupted, by withdrawal symptoms the infant does not require pharmacologic interventions, even when traditional NAS tool scores are elevated. 15 The criteria include the following:…”
Section: The Eat Sleep Console Management Programmentioning
confidence: 99%